Eksplorasi Konsep Geometri Pada Ikan Keturi Piring Dalam Tradisi Masyarakat Melayu Jangkang - Abang Thamren; Sandie; Jamilah (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to determine and examine the geometric ideas contained in the keturi piring fish motif in the heritage of the Jangkang Malay community. Keturi piring fish was chosen as the subject of the study because of its unique physical form. This tradition contains local values ​​related to mathematical concepts, especially geometry, which are reflected both explicitly and implicitly in the patterns and forms of the motif. This study uses an exploratory research design with qualitative methodology. This study uses observation, interview, and documentation study methods to investigate the philosophy and geometry structure of the keturi piring fish motif. The data obtained were then analyzed qualitatively in accordance with the Miles and Huberman methodology, specifically including reduction, presentation, and conclusion/verification. Furthermore, to assess the validity of the data, the researcher used the data triangulation method. The results of the study indicate that the presentation motif of keturi piring fish not only reflects the aesthetics of local culture but also reflects various geometric concepts such as the concepts of algebra, arithmetic, circle, congruence, symmetry, translation, rotation, transformation, and dilation. In addition, this finding reveals that applying geometry concepts to traditional motifs has great potential as a contextual and innovative learning medium in mathematics education, especially to introduce geometry through local wisdom. Keywords: Exploration, geometry, keturi piring fish, jangkang malay community